Beating the Market: The Allure of Unintended Value. (December 2013) - Sela, Aner; Simonson, Itamar; Kivetz, Ran
Consumers face many options that are presented to them as bargains, but in reality, they only subjectively construe a fraction of them as valuable. The authors propose that consumers are particularly attracted to offers they perceive as more valuable than the marketer presumably intended. Consistent with this analysis, six experiments indicate that consumers may perceive customized offers that are presented as tailored to their individual preferences or circumstances as less valuable than offers that seem to fit their preferences and provide value without the marketer's explicit intent. The experiments also suggest that the urge to exploit unintended value reflects a competitive desire to outsmart the market. The findings have theoretical implications for understanding consumers' subjective perceptions of value as well as important practical implications for designing customized offers and targeted promotions.